The story of Charlotte Maxeke : an analysis of how visual arts can be utilised to reflect on race, gender, identity and citizenship in the South African higher educational context - Cele, Kutlwano (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA(VA))--Stellenbosch University, 2018.